Identification of sustainability indicators for oil and petrochemical industries development in southwest coast of Iran - Jaderi, Fereshteh (2012)
This study aims to develop an integrated sustainable development model for oil and petrochemical industries. There are five specific objectives. The first objective is to identify appropriate sustainability model indicators for the city environmental system. The second objective is to identify and evaluate the sustainability indicators for industrial systems. The third is to conduct a risk assessment model of petrochemical companies. The fourth is to determine the sustainability management model in the industry system. The final objective is to develop an integrated sustainable development model for oil and petrochemical industries. The city environmental system was based on Mahshahr, located near the major Petrochemical Economic Free Zone (Petzone) in the southwest coast of Iran. The industrial system investigated was for the Fajr Petrochemical Company (PC), in the Petzone. Two models were developed. The city environmental system included social, economic and environmental subsystems. The industrial system comprised economical, social, environmental, safety, and health subsystems. The city sustainability indicators were identified Delphi group method, Analytical hierarchy structure, and fuzzy logic methods. Quantitative and fuzzy methods are used to evaluate the risk and vulnerability models for industrial system. The city environmental and industrial systems models were then combined to develop an integrated sustainable development model. For the city system total of 218 indicators were identified. The fuzzy model showed that Mahshahr city was at the medium level of sustainability (54.5%). For industrial system a total of 48 indicators were identified. The industrial system model indicated that Fajr PC was also a medium level of sustainability (56.1%). The results of the risk assessment showed a non-critical level of industrial vulnerability. The sustainability management model results, for Fajr PC from qualitative (65.9%) and fuzzy (57.2%) approaches were at the high and medium levels respectively. The integrated sustainability model of Fajr PC showed that the sustainability systems (50%) and sustainability assets (48.56%) were at medium levels. There was no significant difference between the two results. This study quantified and aggregated the city environmental and industrial sustainability systems into an integrated sustainable development model. This allowed the overall sustainability of the oil and petrochemical company within an urban environment to be estimated. This sustainable development study is the first carried out in Iran. The results can serve as benchmarks for the improvement. These indicators and models identified in this study may be employed for other sectors. This type of information can support decision making in order to assist government policymaking towards the sustainable development of coastal zones and oil and petrochemical industries.